SIDE EFFECTS OF ANTIPLATELET DRUGS IN ADULTS - Odiljonova Aziza Bakhtiyor kizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Antiplatelet drugs are cornerstone agents in the prevention and management of cardiovascular and cerebrovascular diseases. They play a crucial role in reducing thrombotic events such as myocardial infarction, ischemic stroke, and peripheral arterial disease by inhibiting platelet aggregation through various biochemical pathways. However, these life-saving medications are associated with a spectrum of adverse effects that range from mild gastrointestinal discomfort to severe bleeding and hematologic complications. This article provides a detailed overview of the mechanisms, clinical manifestations, and pathophysiological basis of antiplatelet drug-related side effects in adults. The discussion encompasses both traditional agents such as aspirin and clopidogrel and newer drugs including prasugrel, ticagrelor, and glycoprotein IIb/IIIa inhibitors. Strategies for minimizing adverse reactions through personalized pharmacotherapy, drug monitoring, and risk stratification are also examined.